The Effect Of Work Motivation And Work Discipline On Employee Performance At PT. Dian Swastatika Sentosa Tbk Karawang - Stefanus Priadinata; Budi Rismayadi; Wike Pertiwi (PT. Berkah Digital Teknologi, 2025)
Purpose of the study — This study aims to analyze the effect of work motivation and work discipline on employee performance at PT Dian Swastatika Sentosa Tbk. Research method—The method used is descriptive quantitative verification with multiple linear regression analysis using SPSS version 25, involving 61 respondents. Result— The results of the study indicate that work motivation (X1) has a significant positive effect on employee performance with a regression coefficient value of 0.504, while work discipline (X2) also has a significant positive effect with a regression coefficient of 0.436. Overall, the regression model shows an R² value of 0.89, indicating that 89% of employee performance variability can be explained by the two independent variables. Conclusion— This study concludes that increasing work motivation and work discipline is very important to improve employee performance. The practical implications of this study indicate the need for companies to implement strategies to increase motivation and discipline in order to achieve optimal performance.